Comment on ‘Non-relativistic treatment of diatomic molecules interacting with generalized Kratzer potential in hyperspherical coordinates’ - Fernández, Francisco Marcelo (2011)
We argue that the textbook method for solving eigenvalue equations is simpler, more elegant and efficient than the asymptotic iteration method applied in Durmus (2011 J. Phys. A: Math. Theor. 44 155205). We show that the Kratzer potential is not a realistic model for the vibration?rotation spectra of diatomic molecules because it predicts the position of the absorption infrared bands too far from the experimental ones (at least for the HCl and H2 molecules chosen as illustrative examples in that paper).